(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This article examines impact of employee satisfaction (ES) on employee performance (EP) utilizing mediation analysis and the created hybrid workplace (HW) model. It was discovered that the parallel and serial mediation effects of the identified components are extremely important in the implementation of hybrid workplace. Certain constructs, such as Work-Life Balance, have a partial mediation influence and might be the subject of future research. The themes that emerged from the conversations emphasized the necessity of the supporting HR practices enabled by a hybrid workplace. Subjective expectations are inherent in the employee-employer relationship, and companies have a significant impact on influencing results of this relationship.